Aspek Hukum Perlindungan Anak dalam Perspektif Hukum Nasional (Lex Jurnalica, 2015)
AbstractLaw No. 39 of 1999 on Human Rights in Chapter III of Human Rights and Fundamental Freedoms of Man in Part Ten concerning the rights of children. The section headed Rights of the Child provides provisions arrangements laid down in 15 (fifteen) article, where Article 52 Paragraph (2) states that children's rights are human rights and for the interests of children's rights that are recognized and protected by the law even since in the womb. Unitary Republic of Indonesia in ensuring the welfare of every citizen one of which is to provide protection of children's rights, which is one of human rights. The Indonesian government in its efforts to ensure and realize the protection and welfare of children is through the establishment of Law No. 23 of 2002 on Child Protection. Child Protection as referred to in Article 1 paragraph 2 of the Act are all activities to ensure and protect children and their rights in order to live, grow, develop and participate optimally in accordance with human dignity, as well as protection from violence and discrimination. Legal protection and the concept of protection for children terterdiri several aspects including; protection of the rights and freedoms of children, protection of children in the judicial process, protection of the welfare of children (in the family environment, education and social environment), the protection of children in matters of detention and deprivation of liberty, the protection of children from all forms of exploitation (slavery, trafficking , prostitution, pornography, trafficking / drug abuse, manipulate children into committing a crime, and so on), the protection of street children, child protection from the consequences of war / armed conflict, the protection of children against violence needs to do special attention to Children Trouble with the Law (ABH) and the need for the application and / or implementation of the basic concept of the protection of children's rights. Key word: Children Troubled With Law (ABH), Human Rights, Legal Protection AbstrakUndang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia dalam Bab III Hak Asasi Manusia dan Kebebasan Dasar Manusia pada Bagian Kesepuluh mengatur mengenai hak anak. Bagian yang mempunyai judul Hak Anak ini memberikan ketentuan pengaturan yang dituangkan ke dalam 15 (lima belas) pasal, dimana dalam Pasal 52 Ayat (2) disebutkan bahwa hak anak adalah hak asasi manusia dan untuk kepentingannya hak anak itu diakui dan dilindungi oleh hukum bahkan sejak dalam kandungan. Negara Kesatuan Republik Indonesia dalam menjamin kesejahteraan pada setiap warga negaranya salah satunya adalah dengan memberikan perlindungan terhadap hak anak yang merupakan salah satu dari hak asasi manusia. Pemerintah Indonesia dalam usahanya untuk menjamin dan mewujudkan perlindungan dan kesejahteraan anak adalah melalui pembentukan Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak. Perlindungan Anak sebagaimana dimaksud dalam Pasal 1 angka 2 Undang-Undang tersebut adalah segala kegiatan untuk menjamin dan melindungi anak dan hak-haknya agar dapat hidup, tumbuh, berkembang, dan berpartisipasi secara optimal sesuai dengan harkat dan martabat kemanusiaan, serta mendapat perlindungan dari kekerasan dan diskriminasi. Perlindungan hukum dan konsep perlindungan bagi anak terterdiri beberapa aspek diantaranya; perlindungan terhadap hak-hak asasi dan kebebasan anak, perlindungan anak dalam proses peradilan, perlindungan kesejahteraan anak (dalam lingkungan keluarga, pendidikan dan lingkungan sosial), perlindungan anak dalam masalah penahanan dan perampasan kemerdekaan, perlindungan anak dari segala bentuk eksploitasi (perbudakan, perdagangan anak, pelacuran, pornografi, perdagangan/ penyalahgunaan obat-obatan, memperalat anak dalam melakukan kejahatan dan sebagainya), perlindungan terhadap anak-anak jalanan, perlindungan anak dari akibat-akibat peperangan/konflik bersenjata, perlindungan anak terhadap tindakan kekerasan perlu dilakukannya perhatian khusus terhadap Anak Bermasalah dengan Hukum (ABH) serta perlunya penerapan dan/atau implementasi konsep dasar terhadap perlindungan hak-hak asasi anak. Kata Kunci: Anak Bermasalah Dengan Hukum (ABH), HAM, Perlindungan Hukum